HUBUNGAN KECEMASAN DENGAN KONTROL ASMA PADA PASIEN ASMA BRONCHIAL - Lina Erlina; Deva Savier Wibisono; Sansri Diah Kurnia Dwidasmara; Yati Tursini (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Control of clinical manifestations of asthma is a term of asthma control. Anxiety is a psychological problem that affects asthma control. Anxiety is a trigger for asthma attacks. The study aims to determine the relationship of anxiety levels with asthma control in bronchial asthma patients. Cross sectional research design. Sampling uses a purposive sampling technique. The number of samples was 73 respondents. Measuring instruments used are the Hamilton Anxiety Rating Scale and the Asthma Control Test. Chi Square method is used in data analysis. The results showed 63% of asthma patients experience anxiety and 61.6% of asthma control patients who are not controlled. The study concluded that there was a significant relationship between anxiety and asthma control, with a p value of 0.010. The need for anxiety control and stress management in an effort to reduce anxiety as an effort to improve asthma control. Keywords: bronchial asthma, anxiety, asthma control